Effect of low molecular weight heparin on bleeding after radical gastrectomy: A retrospective study from a high-volume center in China - Peng Zhou; Yan Hu; Peili Jin; Jinxin Zheng; Fenglin Liu; Zhenbin Shen; Weidong Chen; Kuntang Shen; Zhaoqing Tang; Yihong Sun; Xuefei Wang (Clinical Surgical Oncology)
Background: Although low molecular weight heparin (LMWH) is recommended to prevent venous thromboembolism (VTE) in patients with gastric cancer, it's difficult for surgeons to choose appropriate time to start anti-coagulation because of the risk of surgical field bleeding after radical gastrectomy. We compared the risk of VTE and bleeding between patients receiving LMWH within and beyond 48 ​h after surgery. Methods: The medical records of consecutive cases receiving radical gastrectomy from November 1st, 2017 to October 31st, 2018 in Zhongshan Hospital Gastric Cancer Center were carefully reviewed. Patients receiving LMWH within and beyond 48 ​h after surgery were regarded as Early Group (EG) and Delayed Group (DG), respectively. Incidence of VTE and bleeding complications were compared and risk factors of bleeding were evaluated. Results: Six hundred and sixty-five cases were enrolled, including 465 in EG and 200 in DG. No significant differences of clinicopathological or operative features were observed except for fewer combined resection (DG: 5.0%, EG: 1.9%, P ​= ​0.030) and shorter surgery duration (DG: 194min, EG: 168min, P ​< ​0.001). No patients suffered from deep venous thrombosis or pulmonary embolism in our study. However, postoperative bleeding rate was higher in EG (DG: 1.5%, EG: 7.5%, P ​= ​0.002). Multivariate analysis suggested that EG was the independent risk factor of bleeding (OR: 3.744, 1.13–12.36, P ​= ​0.030). Conclusion: Use of LMWH 48 ​h after radical gastrectomy maybe a good choice for clinical surgeons to reduce postoperative bleeding rate without increasing VTE risk in gastric cancer patients.